Artificial molecular motors in biological applications - Fan, Fuli; Liu, Songshen; Yan, Yuting; Zhang, Peng; Che, Kui (Frontiers in Molecular Biosciences, 2025)
Molecular motors are the cornerstone for the maintenance of living systems and mediate almost all fundamental processes involved in cellular trafficking. The intricate mechanisms underlying natural molecular motors have been elucidated in detail, inspiring researchers in various fields to construct artificial systems with multi-domain applications. This review summarises the characteristics of molecular motors, biomimetic approaches for their design and operation, and recent biological applications.